2015
DOI: 10.1121/1.4934955
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between landscape elements and tranquility evaluation based on eye tracking experiments

Abstract: Visual attention in tranquility evaluations has been examined by eye tracking experiments using audiovisual materials collected in traditional villages of China. The results show that without sound stimuli, the attention areas in tranquility evaluations are more concentrated, compared with those in visual aesthetic quality evaluations. With sound stimuli, the attention areas of tranquility evaluations disperse significantly from those without sound stimuli, where artificial sounds tend to expand the visual att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 20 publications
1
35
0
Order By: Relevance
“…More specifically, such attributes (so called "basic" or "preattentive" features) are available in a primary stage of vision and they are able to guide the selective visual attention process in a "bottom-up" way [63]. Additionally, the drawn of attention in specific buildings or infrastructures (e.g., with different shapes than others) during the observation of different landscapes has also been observed in previous studies (e.g., [64]). Eventually, the examination of the produced heatmaps indicates that observers are able to detect multiple actions that may be presented in a UAV video (e.g., an action of a group of pedestrian when a main human object is presented in a scene).…”
Section: Discussionsupporting
confidence: 58%
“…More specifically, such attributes (so called "basic" or "preattentive" features) are available in a primary stage of vision and they are able to guide the selective visual attention process in a "bottom-up" way [63]. Additionally, the drawn of attention in specific buildings or infrastructures (e.g., with different shapes than others) during the observation of different landscapes has also been observed in previous studies (e.g., [64]). Eventually, the examination of the produced heatmaps indicates that observers are able to detect multiple actions that may be presented in a UAV video (e.g., an action of a group of pedestrian when a main human object is presented in a scene).…”
Section: Discussionsupporting
confidence: 58%
“…Another study indicated that the presence of music can prolong the duration of stay in a tunnel when compared with silence, and classical music caused the longest duration of stay ( Aletta et al, 2016 ). It has also been found that in the case of sound stimulation in the audio–visual environment of the countryside, study participants’ gazing range was demonstrated to be significantly more dispersed than when no sound stimulation was present ( Ren and Kang, 2015 ). Previous studies have mainly focused on the effect of the sound environment on one’s action ( Zakariya et al, 2014 ; Aletta et al, 2016 ; Lepore et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…the matching phenomenon of audiovisual information (Ren and Kang, 2015b), where the untidy 247 family houses scene moderated the uncomfortable audio perception of the artificial sound (house 248 repair sound). 249…”
mentioning
confidence: 99%